Smart Solar Dome Dryer: IoT-Integrated Automatic Hybrid Drying System for Cereal Grains - Hanis Adila Lestari; Luthfi Wahab; Triat Adi Yuwono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
The drying process for cereals is essential to reduce the moisture content of grains to an optimal level of 12%; however, it is often hindered by the unpredictable tropical climate. This study aimed, firstly, to design a solar dome dryer for drying grains using solar energy and, secondly, to develop an automatic control system for a hybrid solar-heated system based on the Internet of Things (IoT). The research started with engineering design, followed by drying test using single-factor of different grains. The Solar Dome Dryer (SDD) was constructed with a lightweight steel frame covered by UV-resistant plastic, sizing 2 × 1 m and with a capacity of 25 kg. It is equipped with an exhaust and heater operating in a hybrid mode during day and night, controlled by DHT22, BH1750, and capacitive soil moisture sensors integrated with a Smart SDD application on a smartphone. Results showed that percentage error, MAE, RMSE, and R² values were below 1%, indicating high sensor accuracy and consistency. The final moisture contents of 12% were achieved in the following grains: rice 4.72 h, red rice 6.20 h, glutinous rice 6.20 h, black glutinous rice 6.62 h, feed maize 7.35 h, sweet maize 7.62 h, glutinous maize 7.27 h, white sorghum 6.20 h, brown sorghum 5.99 h, and red sorghum 5.64 h. ANOVA of drying using SDD was faster than conventional, even while performing drying during rainy conditions.